Marathon running transiently increases c‐Jun NH2‐terminal kinase and p38γ activities in human skeletal muscle - Boppart, Marni D.; Asp, Sven; Wojtaszewski, Jørgen F. P.; Fielding, Roger A.; Mohr, Thomas; Goodyear, Laurie J. (The Journal of physiology, 2000)
1 We examined the pattern of activation and deactivation of the stress‐activated protein kinase signalling molecules c‐Jun NH2‐terminal kinase (JNK) and p38 kinase in skeletal muscle in response to prolonged strenuous running exercise in human subjects. 2 Male subjects (n= 14; age 32 ± 2 years; VO2,max 60 ± 2 ml kg−1 min−1) completed a 42.2 km marathon (mean race time 3 h 35 min). Muscle biopsies were obtained 10 days prior to the marathon, immediately following the race, and 1, 3 and 5 days after the race. The activation of JNK and p38, including both p38α and p38γ, was measured with immune complex assays. The phosphorylation state of p38 (α and γ) and the upstream regulators of JNK and p38, mitogen‐activated protein kinase kinase 4 (MKK4) and mitogen‐activated protein kinase kinase 6 (MKK6), were assessed using phosphospecific antibodies. 3 JNK activity increased 7‐fold over basal level immediately post‐exercise, but decreased back to basal levels 1, 3 and 5 days after the exercise. p38γ phosphorylation (4‐fold) and activity (1.5‐fold) increased immediately post‐exercise and returned to basal levels at 1, 3 and 5 days following exercise. In contrast, p38α phosphorylation and activity did not change over the time course studied. MKK4 and MKK6 phosphorylation increased and decreased in a trend similar to that observed with JNK activity and p38γ phosphorylation. Prolonged running exercise did not affect JNK, p38α, or p38γ protein expression in the days following the race. 4 This study demonstrates that both JNK and p38 intracellular signalling cascades are robustly, yet transiently increased following prolonged running exercise. The differential activation of the p38 isoforms with exercise in human skeletal muscle indicates that these proteins may have distinct functions in vivo.